Preoperative Imaging-Guided Surgical Planning in Complex Pelvic Fractures - Innovations in Traumatology and Radiology for Enhanced Clinical Outcomes: A Systematic Review - Miranda Suárez , Kevin; Fabara Vera , Mateo Daniel; Arias Audor, Giovanni Andres; Serrano Ordóñez , Estefani Mishel; Alava Salamea, Carlos Luis (Arandu UTIC, 2024)
This systematic review will explore role of preoperative imaging-guided surgical planning for the management of complex pelvic fractures. Pelvic fractures occurs in high-energy trauma and cause challenges for intricate anatomy and have a high association with vascular, visceral injuries. Traditional imaging methods frequently fail to capture injury complexity while increasing surgical risks. Recent advancements of imaging technology CT, MRI, 3D reconstructions along with and AI-based predictive models offer enhanced precision in diagnosing and planning surgical interventions with detailed insights into fracture patterns, bone density, and soft tissue damage which enable accurate surgical planning to reduce intraoperative complications and shorten recovery times. We aim to systematically investigate effectiveness of modern imaging techniques with potencies in clinical outcomes, with an emphasis on improved surgical accuracy and patient safety. Analyzing range of studies, we have established evidence-based recommendations for integrating advanced imaging technologies into routine trauma care showing critical role these innovations play in improving both short-term recovery and long-term clinical outcomes for patients having complex pelvic fractures.